Mémoires lesbiennes : le lesbianisme à Montréal entre 1950 et 1972 - Chamberland, Line (Les éditions du remue-ménage, 1996)
Line Chamberland retrace la vie de femmes qui ont eu le courage de leurs amours à une époque où la condamnation sociale du lesbianisme était unanime. À partir de nombreux témoignages, l’auteure démontre de quelle façon s’exerçait le contrôle social du lesbianisme, quel rôle jouait la famille et comment diverses instances comme les institutions religieuses, l’appareil judiciaire et les autorités psychomédicales veillaient à ce que ces femmes se conforment aux diktats, les poussant parfois à la marginalité ou les obligeant à adopter diverses stratégies de dissimulation.
Keywords: 1900-1999; 1950-1959; 1960-1969; 1970-1979; LGBTQIA2+; amérique du nord; amériques; approches et analyses; canada; cours; discipline; droits des femmes*; histoire et politique; hétéronormativité; hétérosexisme; identités LGBTQIA2+; lesbianisme; montréal; pol4212; premier cycle; périodes historiques; queer; québec; régions géographiques; sexualité; shm4000; systèmes d'oppressions; thématiques; violences

Inside the visible: an elliptical traverse of 20th century art in, of, and from the feminine - Zegher, M. Catherine de; Institute of Contemporary Art (Boston, Mass); Kanaal Art Foundation.; Zegher, M. Catherine de; Institute of Contemporary Art (Boston, Massachusetts); Kanaal Art Foundation. (MIT Press, 1996)
Published on the occasion of a major exhibition opening at the Institute of Contemporary Art in Boston, Inside the Visible presents a gendered reading of more than thirty women artists of vastly different background and experience. The work of important yet previously "invisible" figures is highlighted alongside the work of established artists to create a retheorized interpretation of the art of this century. Structured in terms of recurrent cycles over time, Inside the Visible focuses on three periods (the 1930s and 1940s, the 1960s and 1970s, and the 1990s) that anticipated a wave of political repression, nationalism, and xenophopia, often stimulating artistic production that redefined practice. Illustrated essays document each artist in the collection. In addition, four general essays trace the connections among the artists. These take up such issues as why artistic recognition eluded certain artists and why their work is only just becoming visible today. They also address overlapping themes such as gender and sexuality; the intersection of racial, class, ethnic, sexual, and regional identities; and the nature of the relationship between work and viewer.
Keywords: 1900-1999; 1930-1939; 1940-1949; 1960-1969; 1970-1979; 1990-1999; approches et analyses; artistes féministes; arts; cours; discipline; femmes* artistes; har4600; histoire de l'art; histoire et politique; intersectionnalité; premier cycle; périodes historiques; queer; thématiques

The new lesbian studies: Into the twenty-first century - Zimmerman, Bonnie; McNaron, Toni A. H. (Feminist Press at the City University of New York, 1996)
Foreword by Margaret Cruikshank Introduction by Bonnie Zimmerman and Toni A. H. McNaron By celebrating the differences among lesbian scholars and attending to the ways in which the field has been shaped by shifting politics and the emergence of queer studies, this collection challenges the limits of lesbian studies while affirming its value. Forty essays arranged in six parts explore the history of lesbian studies as well as its current impact on conceptions of identity and community, teaching, academic disciplines, university practices, and the development of feminist and queer theories. The collection offers stirring personal testimony; multicultural and international perspectives and established and new voices; strategies for integrating lesbian studies into the curriculum; and contributions from lesbians working in libraries, athletic departments, and students services. Throughout, the contributors address the ways in which lesbian studies has transformed and will continue to transform traditional disciplines, practices, and thought.
https://www.gbv.de/dms/bowker/toc/9781558611368.pdf
Keywords: approches et analyses; histoire et politique; lesbianisme; personnes lesbiennes; queer; thématiques